REACTION TO THE 2016 NEGOTIATIONS HELD IN VIENNA AND ST. PETERSBURG ON THE NAGORNO-KARABAKH CONFLICT ISSUE IN THE DAILY NEWSPAPER ―ZHAMANAK - Ohanyan T., Y. (SUSh Scientific Proceedings, 2025)
The negotiations in Vienna and St. Petersburg are an integral part of the negotiation process on Artsakh issue, which received wide resonance in the daily newspaper ―Zhamanak‖, published in Turkey. The newspaper presents the negotiation process based on information received from Armenia and publications from other international media. ―Zhamanak‖'s publications testify that the newspaper is fully aware of the negotiation process and deeply comprehends the importance of the agreements reached in Vienna and St. Petersburg. The newspaper does not hold out high hopes on Vienna negotiation process, considering that it will remain just a meeting, however, according to the newspaper, the lack of contacts will aggravate the situation. Comparing the problem of Artsakh with Kosovo and other problems, the newspaper considers that the independence of Nagorno-Karabakh must first be recognized by one of the large countries and only then by the Republic of Armenia, otherwise it will be unrealistic and tragic. ―Zhamanak‖ presents the Vienna and St. Petersburg negotiations, as well as the Artsakh problem in general from a pro-Armenian position.